The examination of the heart rate recovery after anaerobic running in soccer players - Taskin, H.; Erkmen, N.; Ccioglu , I. (Collegium Antropologicum, 2014)
The purpose of this study was to examine the heart rate recovery depending on anaerobic running. A total of 23 professional soccer players who were player of Turkish Super Leagues, were examined. Anaerobic Run test was applied to the soccer players and their heart rates were recorded before running, just after running, in 3rd and 6th minutes of recovery period.